"I Hate When They Do That!" Netiquette in Mourning and Memorialization Among Danish Facebook Users. Issue 1 (2nd January 2017) - Sabra, Jakob Borrits
Abstract : By analyzing online practices of mourning and memorialization on Facebook, this article identifies underlying norms behind Danish Facebook users' attitudes towards networked grieving and emotional displays on Facebook. Drawing on the concept "context collapse" and Jakoby's model for social rules of displaying emotions of grief, quantitative and qualitative methods of analysis are combined, through the use of survey techniques and grounded theory. The article helps explain contrasting attitudes to emotional displays on Facebook and significant differences between "netiquettes" of mourning and memorialization. The findings counter popular perceptions of Facebook as a desired online mourning platform.